Effects of exercise training on bone mineral density and some health-related outcomes in HIV conditions: A randomized controlled trial. Issue 50 (11th December 2020) - Ajidahun, Adedayo Tunde; Myezwa, Hellen; Ibeneme, Sam Chidi; Magobotha, Sebastian; Fortwengel, Gerhard; Jingo, Maxwell; Milner, Brenda; Ravat, Sadiya; Okoye, Ifeoma; Schnaid, Edward; Bischoff, Faith
Abstract: Introduction: Human Immunodeficiency Virus (HIV) infection remains prevalent co-morbidity, and among fracture patients. Few studies have investigated the role of exercise interventions in preventing bone demineralization in people who have fractures and HIV. If exercise exposed, HIV-infected individuals may experience improved bone health outcomes (BMD), function, quality of life (QoL). The study will aim to assess the impact of home based exercises on bone mineral density, functional capacity, QoL, and some serological markers of health in HIV infection among Nigerians and South Africans. Methods and design: The study is an assessor-blinded randomized controlled trial. Patients managed with internal and external fixation for femoral shaft fracture at the study sites will be recruited to participate in the study. The participants will be recruited 2 weeks post-discharge at the follow-up clinic with the orthopaedic surgeon. The study population will consist of all persons with femoral fracture and HIV-positive and negative (HIV-positive medically confirmed) aged 18 to 60 years attending the above-named health facilities. For the HIV-positive participants, a documented positive HIV result, as well as a history of being followed-up at the HIV treatment and care center. A developed home based exercise programme will be implemented in the experimental group while the control group continues with the usual rehabilitation programme. The primary outcome measures will be function, gait, bone mineral density, physical activity, and QoL. Discussion: The proposed trial will compare the effect of a home-based physical exercise-training programme in the management of femoral fracture to the usual physiotherapy management programmes with specific outcomes of bone mineral density, function, and inflammatory markers. Trial registration: The study was prospectively registered with the Pan African Clinical Trials Registry (Reference number – PACTR201910562118957) on October 21, 2019. (https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=9425 ).